Bone Tissue Disorders: Healing Through Coordination Chemistry. Issue 67 (19th November 2020) - Barbosa, Jéssica S.; Mendes, Ricardo F.; Figueira, Flávio; Gaspar, Vítor M.; Mano, João F.; Braga, Susana S.; Rocha, João; Almeida Paz, Filipe A.
Abstract: Osteoporosis, Paget's disease and osteosarcoma are a few examples of bone tissue disorders that affect millions of people worldwide. These conditions can strictly limit the lifestyle of patients and may even lead to their demise. To prevent this or, at least, try to manage the situation, there are several treatments available on the market. Notwithstanding, research has been driven by the possibility to improve the existing therapies, as well as to find new approaches that could better respond to these diseases. In this Review the path is shown through which, in recent years, coordination compounds have been prepared and manufactured to be applied in the management of bone tissue disorders. Starting with the design and preparation of the coordination compounds with various dimensionalities, two approaches have been used: (1) they are prepared as three‐dimensional cages that can act as delivery systems for therapeutic substances, or (2) they are constructed/prepared from compounds with intrinsic therapeutic properties. Following this, several strategies have been explored to manufacture the effective delivery to the patients. The versatility of coordination compounds has allowed their use in the preparation of drug tablets, coatings for titanium implants, or even scaffolds for bone tissue engineering. In the end, it becomes clear that these compounds can be a valuable approach to reach a better treatment for bone tissue disorders. Nonetheless, along the road, a few bumps have appeared concerning the therapeutic profile, such as the effect of the structural arrangement or particle size. Abstract : Close to the bone : Metal–organic frameworks, coordination polymers and discrete coordination complexes can be used in the treatment of bone disorders. This Review provides an insight into recent progress in this area.